Propiedades psicométricas del Inventario de Depresión Estado Rasgo (IDER) con una muestra de población general colombiana (2014)
ABSTRACT: This study provides information regarding the psychometric properties of the IDER (Inventario de Depresión Estado/Rasgo) with a non-clinical Colombian sample (N= 1043). Data for validity and reliability are reported. The findings are similar to data obtained with Spanish, American, and Chilean samples. Data from exploratory and confirmatory factorial analyses confirm the bifactorial structure (dysthymia and euthymia) of the instrument. Reliability levels range from .71 to .86. The convergent validity indexes in relation to the CBD are moderate and significant (.59). On the other hand, correlations with the STAI and STAXI-2, as measures of discriminant validity, were lower, although still significant (between .25 and .38 for anxiety and between .25 and .43 for anger). Women obtained higher scores than men, similar to previous studies. The findings from this new sample confirm the adequate psychometric properties of the instrument. Nevertheless, it is important to note that the IDER is valuable as a measure of negative negativity but not as a diagnostic instrument for depression.